Biosynthesis of rhamnolipid by a Marinobacter species expands the paradigm of biosurfactant synthesis to a new genus of the marine microflora - Tripathi, Lakshmi (Microb Cell Fact, 2019)
BACKGROUND: In comparison to synthetically derived surfactants, biosurfactants produced from microbial culture are generally regarded by industry as being more sustainable and possess lower toxicity. One major class of biosurfactants are rhamnolipids primarily produced by Pseudomonas aeruginosa. Due to its pathogenicity rhamnolipid synthesis by this species is viewed as being commercially nonviable, as such there is a significant focus to identify alternative producers of rhamnolipids. RESULTS: To achieve this, we phenotypically screened marine bacteria for biosurfactant production resulting in the identification of rhamnolipid biosynthesis in a species belonging to the Marinobacter genus. Preliminary screening showed the strain to reduce surface tension of cell-free supernatant to 31.0 mN m(−1). A full-factorial design was carried out to assess the effects of pH and sea salt concentration for optimising biosurfactant production. When cultured in optimised media Marinobacter sp. MCTG107b produced 740 ± 28.3 mg L(−1) of biosurfactant after 96 h of growth. Characterisation of this biosurfactant using both HPLC–MS and tandem MS showed it to be a mixture of different rhamnolipids, with di-rhamnolipid, Rha-Rha-C(10)-C(10) being the most predominant congener. The strain exhibited no pathogenicity when tested using the Galleria mellonella infection model. CONCLUSIONS: This study expands the paradigm of rhamnolipid biosynthesis to a new genus of bacterium from the marine environment. Rhamnolipids produced from Marinobacter have prospects for industrial application due to their potential to be synthesised from cheap, renewable feed stocks and significantly reduced pathogenicity compared to P. aeruginosa strains.